Exploring international differences in rates of return to education: Evidence from EU SILC - Maria A. Davia; Seamus McGuinness; Philip O'Connell (The Economic and Social Research Institute (ESRI), 2009)
This paper uses EU-SILC data from 2005 and 2006 to explore the hypothesis that international differences in rates of return to education reflect variations in the level of risk associated with educational investments. While there was some evidence to support this hypothesis with regards to returns to ISCED level 5 qualifications among males, the majority of the variation in international returns was related to distributional impacts. The results suggest that higher rates of return to more advanced qualifications relate to more dispersed distributions among poorly qualified workers which, in turn, raise the returns to credentials further up the educational spectrum.
Keywords: C29; I21; J24; 330; returns to education; dispersion; risk; Bildungsinvestition; Entscheidung bei Risiko; Bildungsertrag; Vergleich; EU-Staaten